Upaya Meningkatkan Pemahaman Konsep Matematika Dengan Model Pembelajaran Conceptual Understanding Procedures (Cups) Berbantuan E-Modul Materi Trigonometri Di Kelas Xi Mipa-1 SMAN 1 Sinunukan - Siregar, Torang; Suparni; Amir, Almira; Adinda, Anita (Lppm Universitas Nurul Hud, 2024)
This research aims to see whether there is an increase in students' ability to understand mathematical concepts by implementing the Conceptual Understanding Procedures (CUPs) learning model assisted by e-modules. This research is classroom action research (PTK), with research subjects of class XI MIPA-1 students at SMAN 1 Sinunukan, Kabupaten Mandailing Natal, totalling 310 people. The object of the research is to examine whether or not the application of the CUPs learning model assisted by e-modules in class This research consisted of 2 cycles, in cycle I based on analysis showed that 22 students (62.810%) met the criteria for learning success, while 13 students (37.14%) did not meet the learning success criteria. Cycle I produced a mean class score of 78.66. Furthermore, in the second cycle there was an increase, namely the total number of students who achieved the criteria for learning success became 36 students (88.107%) or the high category, although 4 students (11.49%) still did not meet the criteria for learning success and the average class score was 86. 38. The research results obtained show that the application of the Conceptual Understanding Procedures (CUPs) learning model assisted by e-modules in trigonometry material improves the ability to understand mathematical concepts in class XI MIPA-1 students at SMAN 1 Sinunukan, Kabupaten Mandailing Natal for the 2022/2023 academic year.